2020
DOI: 10.3390/ijms21031126
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Innate Immunity Mechanisms in the Brain of Alzheimer’s Disease

Abstract: Among environmental factors likely associated with Alzheimer's disease (AD), persistent virus infections, and age-related progressive decline of immune competence might play a pivotal role. However, AD antimicrobial brain immune responses are poorly investigated. The present study focused on genes involved in antimicrobial defenses, especially against virus infections, in the AD brain. In particular, mRNA levels of IRF7, MED23, IL28B, and IFN-α genes were analyzed in hippocampus and temporal cortex brain sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…For instance, a network related to “liver damage” was upregulated in CAST compared to B6 ( Figure 5E ). Genes in this network included Irf7 , Birc3 , Tnfsf10 , Il6 , Serpine1 , and Tab1 (predicted to be the upstream regulator), which have been shown to be DE in brains of AD patients ( Agora Consortium, 2020 ) and identified as targets for therapeutics ( Costa et al, 2017 ; Romagnoli et al, 2020 ; Calandria et al, 2015 ; Riphagen et al, 2020 ; Cantarella et al, 2015 ; Kutz et al, 2012 ; Caraci et al, 2012 ). Based on our data, CAST would be a more appropriate strain than B6 to assess drugs that target genes in this network.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a network related to “liver damage” was upregulated in CAST compared to B6 ( Figure 5E ). Genes in this network included Irf7 , Birc3 , Tnfsf10 , Il6 , Serpine1 , and Tab1 (predicted to be the upstream regulator), which have been shown to be DE in brains of AD patients ( Agora Consortium, 2020 ) and identified as targets for therapeutics ( Costa et al, 2017 ; Romagnoli et al, 2020 ; Calandria et al, 2015 ; Riphagen et al, 2020 ; Cantarella et al, 2015 ; Kutz et al, 2012 ; Caraci et al, 2012 ). Based on our data, CAST would be a more appropriate strain than B6 to assess drugs that target genes in this network.…”
Section: Resultsmentioning
confidence: 99%
“… 151 The Lovheim group could make the association between the ApoE4 genotype, the susceptibility to HSV-1 infection and the occurrence of AD. 152 The virus could remain latent for many years, especially in the in neurons and in the trigeminal ganglia, 153 , 154 and then reactivate each time when the immune defense is diminished by stress, diseases, or other infections. 155 , 156 The virus can easily gain access to the brain by the trigeminus nerve and the olfactory system.…”
Section: Experimental Data Substantially Support the Infection Hypothesis Of Admentioning
confidence: 99%
“… 255 , 256 The interferon regulatory factors (IRF3, IRF7) regulate IFN production. 257 , 258 A recent study by Romagnoli et al 154 found that decreased mRNA levels of IRF7, MED23, IL28B and IFN-α were present in human AD brain hippocampus and temporal cortex samples, with a genetic background of the patients (eg ApoE ε4 and IRF7 A alleles) that could worsen mRNA levels and affect brain immune efficiency. Thus, in the early phase of the infection, this downregulation would favor the decrease of microglia and astrocyte activation and as such mitigate brain damage.…”
Section: Brain Antimicrobial Immunitymentioning
confidence: 99%
“…For instance, a network related to ''liver damage'' was upregulated in CAST compared to B6 ( Figure 5E). Genes in this network included Irf7, Birc3, Tnfsf10, Il6, Serpine1, and Tab1 (predicted to be the upstream regulator), which have been shown to be DE in brains of AD patients (Agora Consortium, 2020) and identified as targets for therapeutics (Costa et al, 2017;Romagnoli et al, 2020;Calandria et al, 2015;Riphagen et al, 2020;Cantarella et al, 2015;Kutz et al, 2012;Caraci et al, 2012). Based on our data, CAST would be a more appropriate strain than B6 to assess drugs that target genes in this network.…”
Section: Natural Genetic Variation Shapes the Transcriptome Landscapementioning
confidence: 95%